Poder + influencia : inteligencia emocional - Bedoya, Victor (BookaVivo, 2022)
Formal authority implicitly carries power. But very few people are aware that there is also an informal power, which is not linked to any position or hierarchy, but capable of exerting great impact. How can you use your power to make it more influential? This book explains how power affects our emotions, our behavior and the way we interact with others. You will learn how to be self-aware to keep your power in check, as well as connect with the right people to create more value and react to abuses of power, so that you can make your legacy deep and lasting.